2017
DOI: 10.1155/2017/2919463
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Bedside Vestibuloocular Reflex Evaluation in the Setting of a False Negative Fistula Test in Cholesteatoma of the Middle Ear

Abstract: Background. False negative fistula testing in patients with chronic suppurative otitis media is a dilemma when proceeding to surgery. It is imperative to rule out a dead labyrinth or a mass effect secondary to the cholesteatoma in an otherwise normally functioning inner ear. We present a case series of three patients in whom a bedside vestibuloocular reflex (VOR) evaluation using a head impulse test was used successfully for further evaluation prior to surgery. Results. In all three cases with a false negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…PIN represents a peculiar finding in LF, although it may show a low diagnostic sensitivity. In fact, it might be underestimated due to a possible complete functional loss of inner ear sensors/afferents or the mass-induced canal plug exerted by concurrent middle ear pathologies might prevent pressure change transmissions to the endolymphatic spaces (16,18,19,28,37). Its pathomechanism is mainly attributed to the stimulation of SC ampulla, according to the site of erosion (14,(20)(21)(22)(23)(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…PIN represents a peculiar finding in LF, although it may show a low diagnostic sensitivity. In fact, it might be underestimated due to a possible complete functional loss of inner ear sensors/afferents or the mass-induced canal plug exerted by concurrent middle ear pathologies might prevent pressure change transmissions to the endolymphatic spaces (16,18,19,28,37). Its pathomechanism is mainly attributed to the stimulation of SC ampulla, according to the site of erosion (14,(20)(21)(22)(23)(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, research dedicated to assessing the results of the video head impulse test in patients with COM is scarce. 3 In a case study of three patients with radiologically and surgically confirmed horizontal SCC fistula secondary to COM, D’Albora et al 34 reported that the head impulse test at the bedside (without video) revealed the presence of refixation saccades in the three patients. Additionally, two of these patients underwent a video head impulse test, which showed a decrease in the VOR gain with consequent covert and overt saccades.…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously, with the development of diagnostic technology, HIT and semicircular canal multi-planar reconstruction (s-MPR) can be used appropriately to increase the positive rate of preoperative diagnosis. Indeed, the findings of intraoperative exploration is an important basis for diagnosis (D'Albora et al, 2017). Yamauchi et al (2014) first reported in 2014 the "underwater" endoscopic labyrinthine fistula closure technique.…”
Section: (See Table 1)mentioning
confidence: 99%